Risk factors for osteoporosis and fractures in rheumatoid arthritis. Issue 3 (September 2022) - Baker, Rahaf; Narla, Radhika; Baker, Joshua F.; Wysham, Katherine D.
Abstract: People with rheumatoid arthritis (RA) have both disease-specific risk factors for osteoporosis and fractures in addition to those that affect the general population. Disease specific risks include directly pathogenic auto-antibodies, chronic exposure to systemic inflammation, and joint damage causing early disability. Risk factors that affect the general population which may have a higher prevalence in RA include smoking, calcium and vitamin D deficiency as well as hypogonadism. Additionally, chronic exposure to glucocorticoids results in reduced bone mineral density and body composition changes which can further increase fracture risk. In this review we discuss these risk-factors for osteoporosis as well as factors that may impact fall and fracture risk in people with RA.